Efficacy and safety of an interleukin 6 monoclonal antibody for the treatment of systemic lupus erythematosus: a phase II dose-ranging randomised controlled trial. Issue 3 (26th September 2016) - Wallace, Daniel J; Strand, Vibeke; Merrill, Joan T; Popa, Serghei; Spindler, Alberto J; Eimon, Alicia; Petri, Michelle; Smolen, Josef S; Wajdula, Joseph; Christensen, Jared; Li, Cheryl; Diehl, Annette; et al.
Abstract : Objectives: This phase II trial evaluated the efficacy and safety of an interleukin (IL) 6 monoclonal antibody for systemic lupus erythematosus (SLE). Methods: Patients with active disease were randomised to placebo or PF-04236921 10 mg, 50 mg or 200 mg, subcutaneously, every 8 weeks with stable background therapy. SLE Responder Index (SRI-4; primary end point) and British Isles Lupus Assessment Group-based Composite Lupus Assessment (BICLA) were assessed at week 24. Post hoc analysis identified an enriched population based upon planned univariate analyses. Results: 183 patients received treatment (placebo, n=45; 10 mg, n=45; 50 mg, n=47; 200 mg, n=46). The 200 mg dose was discontinued due to safety findings and not included in the primary efficacy analysis. The SRI-4 response rates were not significant for any dose compared with placebo; however, the BICLA response rate was significant for 10 mg (p=0.026). The incidence of severe flares was significantly reduced with 10 mg (n=0) and 50 mg (n=2) combined versus placebo (n=8; p<0.01). In patients with greater baseline disease activity (enriched population), the SRI-4 (p=0.004) and BICLA (p=0.012) response rates were significantly different with 10 mg versus placebo. Four deaths (200 mg, n=3; 10 mg, n=1) occurred. The most frequently reported adverse events included headache, nausea and diarrhoea. Conclusions: PF-04236921 was not significantly different from placebo for the primary efficacy end point in patients with SLE. Evidence of an effect with 10 mg was seen in a post hoc analysis. Safety was acceptable for doses up to 50 mg as the 200 mg dose was discontinued due to safety findings. Trial registration number: NCT01405196; Pre-results.